Effectiveness of the 5E learning cycle and problem-based learning in writing scientific article based on TPACK / Khairun Nisa, Syahrul Ramadhan and Harris Effendi Thahar - Khairun Nisa, Khairun Nisa; Ramadhan, Syahrul; Thahar, Harris Effendi (Universiti Teknologi MARA, 2024)
This study investigated the effectiveness of incorporating the 5E learning cycle model and problem-based learning (PBL) to enhance students' scientific article writing skills. The study included 58 participants from Universitas Asahan, employing pre-test and post-test group designs. This study utilized descriptive and experimental research methods to analyze the data. Results indicated that classes that implemented the Technological Pedagogical Content Knowledge/TPACK-based 5E-PBL learning cycle model attained an average score of 86.03, while classes that did not integrate this model achieved an average score of 76.81. Significantly higher mean scores were observed among students exposed to the experimental condition. The normality test results indicated that Lcount < Ltable, where the p-value was > 0.05, validating the normal distribution of data for both experimental and control groups. Additionally, the homogeneity test revealed that Fcount < Ftable, demonstrating sample homogeneity. The findings support the effectiveness of the TPACK-based 5E-PBL learning cycle model in improving students' scientific article writing abilities.